Mpox Outbreak: A Call for Urgent Action and Improved Response Strategies - Majani Edward; Grace Gwanafyo; Elizabeth A. Kimambo; Daniel Basaya (Health Science Reports)
ABSTRACT Introduction The resurgence of mpox presents a significant global public health challenge, especially in non‐endemic regions. Following its initial global spread in 2022, the current outbreak is driven by a newly emerged Clade I, exhibiting atypical clinical manifestations and altered transmission patterns. These changes, coupled with limited immunity in younger populations due to the absence of smallpox vaccination, underscore the severity. As of June 2024, nearly 100,000 cases have been documented worldwide, with Africa experiencing the majority of new cases, highlighting critical gaps in global health preparedness. Methodology This article provides an updated analysis of recent mpox cases, exploring the distinct epidemiological and clinical challenges of the current outbreak. It examines transmission patterns, affected demographics, and obstacles like underreporting to understand the evolving crisis. Results The current outbreak is primarily centered in the Democratic Republic of Congo but poses global transmission risks. The dominance of the more severe Clade I and a significant shift towards human‐to‐human transmission, predominantly through sexual contact (83.3% of cases in males aged 29–41), characterize its epidemiology. Inadequate surveillance and underreporting, particularly in low‐resource settings, obscure the true extent of the outbreak. The analysis reveals the urgent need for a coordinated, multisectoral global response. Conclusion Mpox outbreak underscores critical deficiencies in global health preparedness. An effective response requires an evidence‐based, coordinated approach, integrating technical, social, and financial resources internationally and locally. Key recommendations include strengthening surveillance, improving diagnostics, enhancing equitable vaccine accessibility, and implementing robust anti‐stigma initiatives at all levels. An inclusive, multisectoral collaboration between governments, international organizations, and community leaders is crucial to mitigate the public health, social, and economic impacts of this persistent outbreak.